Many-body effects in the excitation spectrum of weakly interacting Bose-Einstein condensates in one-dimensional optical lattices - Beinke, Raphael; Klaiman, Shachar; Cederbaum, Lorenz S.; Streltsov, Alexej Iwanowitsch (Physical review, 2017)
In this work, we study many-body excitations of Bose-Einstein condensates trapped in periodic one-dimensional optical lattices. In particular, we investigate the impact of quantum depletion onto the structure of the low-energy spectrum and contrast the findings to the mean-field predictions of the Bogoliubov-de Gennes (BdG) equations. Accurate results for the many-body excited states are obtained by applying a linear-response theory atop the multiconfigurational time-dependent Hartree method for bosons equations of motion. We demonstrate for condensates in a triple well that even weak ground-state depletion of around 1% leads to visible many-body effects in the low-energy spectrum, which deviates substantially from the corresponding BdG spectrum. We further show that these effects also appear in larger systems with more lattice sites and particles, indicating the general necessity of a full many-body treatment.
Received 20 December 2016; published 5 June 2017
Gesehen am 10.10.2018